Laxity testing of the shoulder: A review - Bahk, M.; Keyurapan, E.; Tasaki, A.; Sauers, E. L.; McFarland, E. G. (The American Journal of Sports Medicine, 2007)
Laxity testing is an important part of the examination of any joint. In the shoulder, it presents unique challenges because of the complexity of the interactions of the glenohumeral and scapulothoracic joints. Many practitioners believe that laxity testing of the shoulder is difficult, and they are unclear about its role in evaluation of patients. The objectives of the various laxity and instability tests differ, but the clinical signs of such tests can provide helpful information about joint stability. This article summarizes the principles of shoulder laxity testing, reviews techniques for measuring shoulder laxity, and evaluates the clinical usefulness of the shoulder laxity tests. Shoulder laxity evaluation can be a valuable element of the shoulder examination in patients with shoulder pain and instability.